The Concept of Good Faith in Criminal Law - (:unkn) unknown (ISTANBUL UNIV, 2020)
Good faith is unfamiliar to criminal law because it is a private law-based concept. In criminal law, the concept of good faith has no normative counterpart in crime theory. Moreover, the doctrine of criminal law does not include the notion of goodwill within the theory of crime. However, since the concept of good faith does not have a normative counterpart in crime theory, it is not possible to accept it as a form of appearance of the moral element of the crime or as a form of view of the moral element, nor it is able to substitute intention. Because the intention is the deliberate and desired realization of the objective elements of the crime, it has a completely different meaning and function to the concept of good faith.
Keywords: Good faith; criminal law; moral element